The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1017/cjn.2017.246
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Genetic Disorders and GLUT1 Deficiency in a Ketogenic Diet Clinic

Abstract: Between July of 2012 and December of 2014, 39 patients were enrolled prospectively to investigate the prevalence of glucose transporter 1 (GLUT1) deficiency in a ketogenic diet clinic. None of them had GLUT1 deficiency. All patients seen in the same clinic within the same period were reviewed retrospectively. A total of 18 of these 85 patients had a genetic diagnosis, including GLUT1 deficiency, pathogenic copy number variants, congenital disorder of glycosylation, neuronal ceroid lipofuscinosis type II, mitoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 9 publications
1
3
0
Order By: Relevance
“…Ramm-Pettersen ( 29 ) demonstrated following the long-term observation of patients with GLUT1-DS, that those who were diagnosed and started the KD within a few months after birth had better psychomotor development, while those who commenced the KD later significantly lagged behind their peers. This conclusion has also been verified by other studies ( 11 , 22 ).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Ramm-Pettersen ( 29 ) demonstrated following the long-term observation of patients with GLUT1-DS, that those who were diagnosed and started the KD within a few months after birth had better psychomotor development, while those who commenced the KD later significantly lagged behind their peers. This conclusion has also been verified by other studies ( 11 , 22 ).…”
Section: Discussionsupporting
confidence: 90%
“…Generalized epileptiform spike-wave patterns are the most common. Hewson et al ( 22 ) reviewed the seizure patterns of 99 patients with GLUT-DS, of whom 89% had extensive spikes or spike-wave electrical activity on EEG. Of all seizure types, generalized tonic-clonic seizures are the most common, and other heterogeneous seizure types, including absence, myoclonic and tonic-clonic seizures have also been reported ( 23 ).…”
Section: Discussionmentioning
confidence: 99%
“…This (Vanoye et al, 2014) *Non genetic origin mutations reported: Mutations described through clinical diagnosis, but the mutation type (Mendelian or de novo) were not reported, mainly due to the lack of parents to perform genotyping and difficulty in contacting the family. DII (S1) Missense NR (Butler et al, 2017b;Hewson et al, 2018;Lindy et al, 2018;Costain et al, 2019;Johannesen et al, 2019) T767I DII (S1) Missense Decreased current density Increased current amplitude provokes by voltage ramp protocol (Estacion et al, 2014;Gardella et al, 2018;Lindy et al, (Fung et al, 2015;Zhang et al, 2015;Lindy et al, 2018;Kim et al, 2019;Tsang et al, 2019;Pan and Cummins, 2020;Schreiber et al, DIII (S6)-DIV (S1) Missense NR (Pons et al, 2018;Denis et al, 2019) G1475R DIII (S6)-DIV (S1) Missense Enhanced persistent current (Hussain et al, 2016;Ortiz Madinaveitia et al, 2017;Parrini et al, 2017;Wang et al, 2017a;Gardella et al, 2018;Lindy et al, 2018;Xiao et al, 2018;Kim et al, 2019;Trivisano et al, 2019;Zaman et al, 2019;Ranza et al, 2020;Schreiber et al, 2020) G1476S DIII (S6)-DIV (S1) Missense NR (Lindy et al, 2018) I1479V DIII (S6)-DIV (S1) Missense NR (Larsen et al, 2015;Lindy et al, 2018;Schreiber et al, 2020) E1483K DIII (S6)-DIV (S1) Missense NR (Johannesen et al, 20...…”
Section: Nav16mentioning
confidence: 99%
“…The prevalence of GLUT1DS ranged from 0.9 to 2.4% in our previous studies. 8,9,12 Prior to 2015, there were two patients diagnosed with GLUT1DS, known to us at our institution. Since the availability of targeted next-generation sequencing panels and whole-exome sequencing in clinical settings, we have confirmed the diagnosis of GLUT1DS in more than 10 patients at our institution.…”
Section: Discussionmentioning
confidence: 99%